2014
DOI: 10.1371/journal.pone.0089600
|View full text |Cite|
|
Sign up to set email alerts
|

Age-Related Macular Degeneration and the Incidence of Cardiovascular Disease: A Systematic Review and Meta-Analysis

Abstract: ImportanceResearch has indicated some shared pathogenic mechanisms between age-related macular degeneration (AMD) and cardiovascular disease (CVD). However, results from prior epidemiologic studies have been inconsistent as to whether AMD is predictive of future CVD risk.ObjectiveTo systematically review population-based cohort studies of the association between AMD and risk of total CVD and CVD subtypes, coronary heart disease (CHD) and stroke.Data SourcesA systematic search of the PubMed and EMBASE databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 41 publications
1
40
1
2
Order By: Relevance
“…192 Human histopathological studies suggest that M2 macrophages 193 are likely activated in later AMD stages rather than in early stages 194 [35,36]. Thus, immune responses evoked by drusen-induced 195 inflammation likely play a central role in the pathogenesis of 196 AMD. The mechanism seems has many similarities with that of 197 atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…192 Human histopathological studies suggest that M2 macrophages 193 are likely activated in later AMD stages rather than in early stages 194 [35,36]. Thus, immune responses evoked by drusen-induced 195 inflammation likely play a central role in the pathogenesis of 196 AMD. The mechanism seems has many similarities with that of 197 atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…[195]. A systematic review and meta-analysis of 773 population-based cohort studies suggest that early AMD was asso-774 ciated with a future risk of CVD events, including coronary heart 775 disease and stroke [196]. C-reactive protein (CRP) is an inflamma-776 tory marker known for the association with cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…The baseline presence of AMD did not predict occurrence of CHD or CVD in the Multi-Ethnic Study of Atherosclerosis (MESA, [123]) full population, but late AMD did associate with both CVD and CHD in a subgroup comprised of older (65+) white participants. In a meta-analysis published in 2014 of eight prospective and five retrospective studies, Wu et al [124] reported that patients with early AMD had an increased risk for CVD and for CHD. When they narrowed the analysis to include only the prospective studies, they also observed that subjects with late AMD had an increased risk for CVD.…”
Section: Epidemiology Of Cardiovascular Health and Amdmentioning
confidence: 99%
“…Az -intervencióra szorult, illetve azon átesett -ischaemiás szívbetegségben szenvedők 22%-ában alakult ki AMD. A korai és késői AMD az elkövetkező cardiovascularis betegség független előrejelzője, az összefüggés sokkal erősebb a késői AMD esetében [74].…”
Section: Az Emberi éRrendszer Egységessége éS Egylényegűségeunclassified